2021
DOI: 10.1002/dad2.12190
|View full text |Cite
|
Sign up to set email alerts
|

P‐tau/Aβ42 and Aβ42/40 ratios in CSF are equally predictive of amyloid PET status

Abstract: Introduction: Measurement of amyloid beta (Aβ40 and Aβ42) and tau (phosphorylated tau [p-tau] and total tau [t-tau]) in cerebrospinal fluid (CSF) can be utilized to differentiate clinical and preclinical Alzheimer's disease dementia (AD) from other neurodegenerative processes. Methods: CSF biomarkers were measured in 150 participants from the Mayo Clinic Study of Aging and the Alzheimer's Disease Research Center. P-tau/Aβ42 (Roche Elecsys, Fujirebio LUMIPULSE) and Aβ42/40 (Fujirebio LUMIPULSE) ratios were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 47 publications
(122 reference statements)
8
44
2
Order By: Relevance
“…The p-tau181/Aβ1-42 ratio has long been considered to have the best statistical power of the CSF markers for representing AD, as it incorporates both hallmarks of the AD disease pathway and represents a later stage of the disease pathway. Indeed this ratio in CSF has helped identify late stage changes in synaptic and neuronal degradation markers and inflammatory markers associated with AD [37], as well as show high concordance with Aβ-PET [15][16][17]20]. Here analyses of the plasma markers at a second time point in this study showed increased performance of all markers, including the p-tau181/Aβ1-42 ratio, at predicting amyloid status at Assessment 2, which may reflect further accumulation of positive biomarker signals compared to a static baseline in the amyloid negative cohort.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The p-tau181/Aβ1-42 ratio has long been considered to have the best statistical power of the CSF markers for representing AD, as it incorporates both hallmarks of the AD disease pathway and represents a later stage of the disease pathway. Indeed this ratio in CSF has helped identify late stage changes in synaptic and neuronal degradation markers and inflammatory markers associated with AD [37], as well as show high concordance with Aβ-PET [15][16][17]20]. Here analyses of the plasma markers at a second time point in this study showed increased performance of all markers, including the p-tau181/Aβ1-42 ratio, at predicting amyloid status at Assessment 2, which may reflect further accumulation of positive biomarker signals compared to a static baseline in the amyloid negative cohort.…”
Section: Discussionmentioning
confidence: 89%
“…For example plasma Aβ1-42 and the Aβ1-42/1-40 ratio predict brain Aβ burden, and tau measured at different phosphorylation sites (threonine181 (p-tau181), threonine217 (p-tau217), threonine231 (p-tau231)) shows concordance with CSF p-tau levels (concordance ~0.8) and can predict Aβ-PET burden (AUC values ranging from 0.8 through 0.9) [9][10][11][12][13][14]. Clinical-pathological models show that understanding about the presence and severity of AD is improved when markers of amyloid and tau levels are considered simultaneously [15][16][17][18], however, to date, only one small study has investigated how combinations of plasma levels of Aβ and p-tau relate to Aβ-PET burden [19]. The first aim of this study was to investigate whether two different plasma p-tau markers (p-tau181 and p-tau231), incorporated into a ratio with Aβ, can improve predictions of Aβ burden over single analytes in comparison to PET or CSF sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Current results of the association of the EV concentration/size ratio with the p-Tau 181/Aβ 42 ratio, as CSF biomarkers of AD [42], are in this direction. The EV concentration/size ratio with the p-Tau 181/Aβ 42 ratio correlation was found for the entire PTS group but the stratified analysis for dementia diagnostic categories revealed that this effect was driven by the AD group.…”
Section: Discussionmentioning
confidence: 98%
“… 27 Second, the cognitive decline associated with two AD proteinopathies, using the ratio of tau pathology to Aβ, was exaggerated in those with severe asthma, in line with previous reports that the ratio of these two biomarkers was more sensitive and specific in terms of amyloid PET agreement than the individual biomarkers. 51 , 52 The association of severe asthma with elevated α‐synuclein is less specific to AD. Even though α‐synuclein is considered useful for the differential diagnosis of AD when combined with other biomarkers 53 and may contribute to AD pathophysiology, it is also present in other forms of dementia.…”
Section: Discussionmentioning
confidence: 99%